Personal contact networks: an overview and application - Hill, Jimmy (Henry Stewart Talks, 2008)
An introduction to personal contact networks, Significance of personal networks for marketing in the context of small to medium sized enterprises (SMEs), Inter-organisational relationships (IORs) as a logical development of PCNs